A Systematic Literature Review on the Branches and Schools of Philosophy and Their Contemporary Relevance - Angraini, Dewi; Sunayah, Sunayah; Astria, Yeni; Jelestari, Nerma; Septi, Elni (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to identify and analyze the main schools and branches of philosophy and explain how each contributes to the development of human thought. The research employs a systematic literature review method using databases obtained from Google Scholar. Researchers applied criteria to collect journal article data, including article types, journals published within the last four years, and keywords such as schools of philosophy, branches of philosophy, and philosophy. The results show that a total of fifteen research articles discussed schools and branches of philosophy. This study aims to enhance our understanding of various branches and schools of philosophy and how they help shape the framework of thought and decision-making processes in various aspects of life. This research highlights that the main branches of philosophy, including ontology, epistemology, ethics, logic, axiology, philosophy of education, and philosophy of science, each focus on essential aspects of understanding the world and human life. Various schools of philosophy, including materialism, realism, idealism, empiricism, rationalism, existentialism, and others, offer different perspectives on the world and the knowledge of it as we understand today.